Human capital as a tool of organization competitiveness assessment - Biliavskyi , V. M. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2017)
The methodical tools to assess the value of the human capital of an organization, which allow management of the organization to take steps to build efficient operational process have been systematized. The matrix model of evaluation of human capital of the organization has been investigated, that corresponds to each characteristic of these models, which provide the fundamental changes in the structure and functionality of departments of the organization. The essence of evaluation models of the human capital of the organization that allows management to take steps to build efficient and competitive organization has been characterized. The parameters of reserve evaluation and the increase of the value of human capital of the organization have been investigated. They are based on the components that characterize the current stage of the development of domestic organizations. The above mentioned approach to assessment of changes in the value of human capital can be regarded as one example of the search for solutions to the problem that will be used in the future to create objective conditions and methodological basis for further study of this issue.